Socio-demographic determinants of access to climate change information among tomato growing farmers in Mvomero district, Tanzania - Sanga, Evaristo Eliakim; Elia, Emmanuel F. (University of Dar es Salaam Library Journal, 2021)
This study investigated tomato farmers ' access to climate information in Mvomero District in Tanzania. This study used mixed approach where both quantitative and qualitative methods were used. The study comprised of 60 farmers ' who were systematically randomly selected. Questionnaires, focus group discussions (FGDs), and in-depth interviews were the methods used in data collection. Quantitative data were analysed by using SPSS while content analysis was used for qualitative data. Key findings show that majority of farmers use radio as a source of climate change information. The study discovered that gender, marital status, age, level of education and income were the socio-demographic factors influencing access to climate change information. The study concludes that socio-demographic factors influence farmers ' adaptation to climate change. The study recommends the establishment of ICT climate change information systems that can provide timely, relevant, and reliable climate change information to farmers. The study also suggests the use of mobile phone technology to reach out a wider population of farmers.